Developing a project portfolio selection model for contractor firms considering the risk factor - Abbasianjahromi, Hamidreza; Rajaie, Hossein (Journal of Civil Engineering and Management, 2012)
Regarding to the high importance of project selection in the project life cycle, solving bid/no-bid problems, especially in the construction industry, is a subject of most recent research. Portfolio selection has been the most interesting area in the last two decades in management research but there is poor investigation in the construction industry. Taking into account the risk, which is inherent in the construction industry and especially in the project selection phase is inevitable. This paper intends to propose a model for project selection and developing two main concepts including company portfolio and risk. The main innovation of this paper is presenting a new framework, which attempts to optimize project selection based on the endurable risk level of a company with regard to the existing portfolio. Considering the user-friendly characteristic of the model, this paper has applied the fuzzy multi criteria decision-making approaches. Finally, the model is implemented in a real case study.